The Accountability Principle in Personal Data Protection in Sweden and Indonesia - Yuspin, Wardah; Wardiono, Kelik; Budiono, Arief; Prakoso, Andria Luhur; Rajput, Trisha (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
Digital transformation presents significant challenges in safeguarding the personal data of banking customers, particularly when banks collect and manage extensive personal information without ensuring adequate protection. This study examines the implementation of the accountability principle by personal data controllers within the banking sector. The objective is to assess how far this principle has been integrated into the obligations stipulated by data protection regulations. Using a qualitative legal research method combined with a comparative approach, this study analyzes the Personal Data Protection Law (PDPL) in Indonesia and the General Data Protection Regulation (GDPR) in Sweden. The findings reveal that Indonesia’s PDPL still demonstrates several deficiencies, including limited data leakage notifications, lack of transparency in third-party data disclosure, insufficient information technology security responses, and inefficient data updates. Similarly, under the GDPR framework, challenges persist in managing data shared with third parties and in providing timely written notices in cases of data breaches. The study concludes that the weaknesses identified in both jurisdictions highlight the need for strengthening the accountability principle to enhance the effectiveness of personal data protection in the banking sector. Reinforcing this principle will ensure greater responsibility among data controllers and foster public trust in digital financial systems.